Ways of Seeing Early Modern Decorative Textiles. (2nd January 2016) - Richardson, Catherine; Hamling, Tara
Abstract: The article introduces and contextualises this special issue on 'Ways of Seeing Early Modern Decorative Textiles', which comprises a series of essays that draw on the activities, research findings and insights of an Arts and Humanities Research Council-funded research network, 'Ways of Seeing the English Domestic Interior, 1500–1700: The Case of Decorative Textiles'. Critically evaluating the results of the network's findings, the paper situates them within a broader investigation of the role of decorative textiles in shaping the experience of domestic interiors in the past and present, and explores new ways of reading such objects in the context of the household. It examines the historiography and current range of approaches to the study, interpretation and exhibition of historic textiles, and analyses the insights offered by bringing together different disciplinary and professional perspectives. It argues for the key significance of these textiles for both historical and modern perceptions of the domestic interior and for the importance of collaborative, cross-disciplinary approaches to researching them in order to understand how they functioned in the early modern period and to inform new directions for their display and presentation in the present.